Zavarovanje odgovornosti članov organov vodenja in nadzora družbe - Srše, Dejan (Pravni letopis, 2019)
Directors and Officers of the company are liable for its negligent acts and omissions with all their personal assets. Personal liability of Directors and Officers represents a risk for them that can be transferred to the insurance company by entering into an insurance contract. The insurance protection for these cases is a Directors & Officers Liability Insurance (D&O Insurance). Such insurance may be stipulated by the company for its members of the management and control bodies (corporate D&O insurance), but it can also be concluded by individual member of such body by himself (personal D&O insurance). By concluding corporate D&O insurance, the company does not provide protection only to its members of the management and supervisory bodies, but also provides protection indirectly to itself, in case if the damage to the company is caused by the person, who is responsible for company`s management or control.
Keywords: corporate D&O insurance; D&O liability insurance; direktorji; gospodarske družbe; liability for damages; members of management and supervisory bodies; nadzorni organi; odškodninska odgovornost; personal D&O insurance; zavarovanje